2018
DOI: 10.1016/j.jshs.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Fitness and health benefits of team handball training for young untrained women—A cross-disciplinary RCT on physiological adaptations and motivational aspects

Abstract: PurposeThe present study evaluated the effects of regular participation in small-sided team handball training on body composition, osteogenic response, physical performance, and cardiovascular risk factors, as well as well-being and motivation, in young untrained women.MethodsTwenty-eight untrained 20- to 30-year-old women were randomized to a handball training group (HG; n = 14, height 170 ± 5 cm, weight 73 ± 11 kg, VO2peak 37.7 ± 4.1 mL/min/kg) that trained 1.7 ± 0.3 times per week over 12 weeks (70 min 4 v … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
51
3
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 44 publications
14
51
3
8
Order By: Relevance
“…In terms of engaging in activities, our results are in line with previous reviews 33 and original research studies showing that social engagement, 78 engaging in creative activities, 79 or various sport or leisure activities [29][30][31][32][80][81][82][83][84] are positively associated with a number of outcomes related to positive mental health and wellbeing. However, the relationship between the Act predictor and the outcome on LS did not reach statistical significance.…”
Section: Contextualization Of Findingssupporting
confidence: 90%
“…In terms of engaging in activities, our results are in line with previous reviews 33 and original research studies showing that social engagement, 78 engaging in creative activities, 79 or various sport or leisure activities [29][30][31][32][80][81][82][83][84] are positively associated with a number of outcomes related to positive mental health and wellbeing. However, the relationship between the Act predictor and the outcome on LS did not reach statistical significance.…”
Section: Contextualization Of Findingssupporting
confidence: 90%
“…In the past decade, a number of studies have shown that soccer training organized as small-sided games led to a broad spectrum of positive health outcomes in both young and older adults, 12 as well as in people with lifestyle diseases. 13 , 14 , 15 , 16 , 17 , 18 Recently, other team games such as team handball, 19 basketball, 20 and floorball 21 , 22 have been shown to demonstrate positive health effects on untrained young women, post-menopausal women and middle-aged men. Vorup et al.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand in elderly Indian female population, fat mass was positively correlated with BMD (T-score) measured by ultrasound bone densitometry (Chowdhury and Bandyopadhyay 2014). Due to the fact that our study was performed in young women (Hornstrup et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These training elements are kinds of physical activities which have a positive effect on the bone health condition (Turner and Robling 2003). The literature review of the topic indicates the positive effects of handball training on the BMD in teenagers (Boshnjaku et al 2015;Mrabet et al 2013) and young women (Hornstrup et al 2018). On the other hand, the anthropometric profile of female handball players demonstrates increased musculature and skeletal robustness (Granados et al 2007), which is probably related to BMD.…”
Section: Methodsmentioning
confidence: 99%